How do you solve the equation e^2x - 2e^x - 3 = 0 ?

This is a 'quadratic in e^x'. The easiest way to recognise this when starting problems like this is to let y=e^x. As you practice problems like this, you will find yourself moving away from this step. But it is a useful illustration for the concept. Since y=e^x, y^2=e^2x. By substituting these facts into the equation, the equation becomes: y^2 - 2y - 3 = 0 This should now be in a more recognisable format, as quadratics like these will have come up in the Higher Specification for GCSE, or the C1 module in A-level. Assuming that this concept is well understood: This becomes: (y+1)(y-3)=0 Then: y = -1, or y = 3. Since y=e^x: e^x = -1, e^x = 3. By sketching a graph of e^x, it is evident that there are no solutions of e^x = -1. But by using logarithms, we can solve e^x = 3. This gives us our only solution: x = ln3.

Answered by Lewis C. Maths tutor

14053 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

If the functions f and g are defined: f: x--> x/5 + 4 g : x--> 30x + 10. what is x, if fg(x) = x. ?? What would fgf(x) = x^2 be??


Given that dy/dx=6-8x+x^4 and that x=1 when y=4. Find an expression for y in terms of x.


Differentiate x^3+ x^2+2=y


Solve the following equation by completing the square: x^2 + 6x + 3 = 0.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences